Cerebral Oxygenation as a Monitoring Parameter for Mortality During Venoarterial Extracorporeal Membrane Oxygenation. Issue 4 (May 2019) - Kim, Hyoung Soo; Ha, Sang Ook; Yu, Kyung-Ho; Oh, Mi Sun; Park, Sunghoon; Lee, Sun Hee; Han, Sang Jin; Kim, Hyun-Sook; Chang, In Bok; Ahn, Jun Hyong
Abstract : There are no recommended guidelines for monitoring parameters during venoarterial extracorporeal membrane oxygenation (V-A ECMO). We evaluated whether regional cerebral oxygen saturation (rScO2 ) could be a monitoring parameter for mortality during V-A ECMO. We retrospectively searched our database for adult patients who underwent V-A ECMO between April 2015 and October 2016 and identified 21 patients with rScO2 data. Their baseline and clinical characteristics during the first 7 days (vital signs, arterial blood gas results, ECMO variables, rScO2, Swan-Ganz catheter parameters, transthoracic echocardiography parameters, and outcomes) were collected and evaluated for associations with 28 day mortality. The survivor group (12 patients, 57.1%) had higher rScO2 values and lower lactate levels, compared with the nonsurvivor group (nine cases, 42.9%) during the first 7 days. The areas under the receiver operating characteristics curves were 0.87 for right rScO2 ( p < 0.001) and 0.86 for left rScO2 ( p < 0.001). The optimal cutoff values for right and left rScO2 were 58% (sensitivity: 78.7%, specificity: 83.3%) and 57% (sensitivity: 80.0%, specificity: 70.8%), respectively. Kaplan–Meier analysis revealed that the risks of 28 day mortality were higher among patients with a right rScO2 of <58% and a left rScO2 of <57%, compared with patients with a right rScO2 of ≥58% and a left rScO2 of ≥57% (both, p < 0.001). We suggest that rScO2 may be used as a monitoring parameter for 28 day mortality among patients undergoing V-A ECMO.